Flipped classroom for teaching digestive system to high school students: Performance, perception and inquiry competence level - Roberto Reinoso Tapia; Miguel Ángel Collazos Martínez; María del Carmen Martínez Martínez; Jaime Delgado Iglesias (OmniaScience, 2021)
This article presents an educational experience with 30 high school students based on the flipped classroom methodology and inquiry-based learning on aspects related to the pathophysiology of the digestive system during the 2017/2018 academic year. The main goal of this study was to investigate the effectiveness and acceptability of the flipped classroom approach at this educational level. This case study was also used to assess the level of inquiry competence that high school students present when they have to carry out a research project and the main difficulties encountered in carrying it out. The results of the study show that the experience was clearly positive, since there was not only a significant improvement in student learning but also greater autonomy for students to work with the content, prepare for classes and actively participate in the tasks or practical activities that take place in the classroom, demonstrating its applicability in high school classrooms. The results also indicate that the students perceived advantages in their learning after experiencing the flipped classroom pedagogical model. Most of the students presented serious difficulties in carrying out their research work, probably due to a lack of experience when facing each of the stages that make up the process of inquiry.